Local structure of Cu(I) ions in the MOR zeolite: A DFT-assisted XAS study. (October 2020) - Buono, C.; Martini, A.; Pankin, I.A.; Pappas, D.K.; Negri, C.; Kvande, K.; Lomachenko, K.A.; Borfecchia, E.
Abstract: We combine in situ XAS and DFT to determine the local structure of Cu(I) ions in the Cu-exchanged mordenite (MOR) zeolite, one of the most promising materials for the selective oxidation of methane to methanol. Data analysis points to a quasi-linear coordination geometry in the MOR side pocket and suggests that ca. 20% of the Cu-ions exist as coupled di-copper(I) species, paving the way for more detailed structural refinements. Highlights: DFT-assisted XAS allowed determining the local structure of Cu(I) ions in Cu-MOR. Data analysis reveals quasi-linear Cu(I) sites coordinated to two framework oxygens. High levels of disorder are detected in the second coordination sphere of Cu(I). EXAFS supports long-range Cu−Cu contributions involving ca. 20% of the Cu ions. Future studies will target to O2 reaction with the Cu(I) species characterized here.